Asymptomatic bacteriuria among HIV positive pregnant women (2010)
The prognostic significance of asymptomatic bacteriuria resides in the observation that the prevalence is, relatively, high in persons with certain medical conditions, such as diabetes mellitus and pregnancy. This prevalence might, even, be higher in patients with human immunodeficiency virus infection. Hence, this study set out to determine the prevalence of asymptomatic bacteriuria among symptom free and newly enrolled HIV infected pregnant women attending PMTCT unit of Antiretroviral Clinic of University College Hospital, Ibadan, Nigeria between 1st May and 30th September 2007. Information was obtained on the socio-demographic characteristics of the subjects, CD4 count and viral load. Microbial culture was carried out on aseptically collected urines from the patients. Statistical analysis was done with SPSS 12 package. There were 161 analyzable samples from the participants. The mean age and gestational age at presentation of participants was 30.49 ± 4.3 years and 27.3 ± 3.2 weeks, respectively with modal parity of 2. Twenty-five (15.5%) of the urine samples significantly grew bacteria. The CD4 cells were significantly lower and the viral loads significantly higher (250.52 vs. 355.57 cells/mm3; 88,731 vs. 55,384 copies/ml; p = <0.0000) for the urine culture positive patients. Eshcherichia coli were isolated in 48%, Proteus in 16.0%, Klebsiella in 8.0% and Staphylococcus aureus in 28.0% of the urine positive cultures. The study showed that the prevalence of asymptomatic bacteriuria among PLWHAs is high. The microbial isolate from the urine samples were not different from those of HIV-negative patients.